O comércio por vias internas e seu papel sobre crescimento e desigualdade regional no Brasil - Aline Souza Magalhaes (2009)
This thesis deals with interregional trade in the Brazilian Economy, estimating the role of interregional trade on efficiency, international competitiveness, national welfare and regional inequality. Thus, the dissertation seeks to evaluate the importance of trade flows between the Brazilian states, and measure the most relevant links. Our modeling encompasses much detail. Firstly, we use a large-scale multi-regional computable general equilibrium (CGE) model of Brazil (IMAGEM-B). The model is bottom-up for Brazil's 27 states and disaggregated in 36 sectors. It has the ability to deal with shocks on policies that originate in the regions and the detailed treatment of transport and trading margins, with the possibility of substitution between four modes of transport. Applying the CGE model we explore the impacts of reducing transport costs among Brazilian states, identifying the most relevant links for different economic goals (national growth, production costs, regional inequality, national welfare and regional growth, specifically for the Northeast). We find that the trade among most developed states have impact on national growth, welfare-state and international competitiveness, but can increase regional inequality. Furthermore, in order to summarize and to analyze the main results for the Brazilian states, we use the concepts of Market Access and Supplier Access of the New Economic Geography.